Problematika Guru Dalam Menerapkan Kurikulum Merdeka - Windayanti Windayanti; Mihrab Afnanda; Ria Agustina; Emanuel B S Kase; Muh Safar; Sabil Mokodenseho (Departement of Mathematics Education, 2023)
This study aims to describe the teacher's problems in implementing the independent curriculum in schools. This study uses a literature review or literature review approach. The results of this study indicate that there are many problems that become obstacles for teachers in schools. In the independent learning curriculum, teachers are more required to be creative in making or designing the learning process so that learning goes according to what is determined by the Minister of Education. The results showed that: First, SMA Negeri 3 Sungai Full has implemented the Independent Learning Curriculum by implementing project-based learning, diagnostic, formative and summative assessments in learning. Second, the teacher's problems in implementing the Free Learning Curriculum in planning, implementing and evaluating learning are difficulties analyzing CP, formulating TP and compiling ATP and Teaching Modules, determining learning methods and strategies, lack of ability to use technology, lack of ability to use learning methods and media, materials teaching is too broad, determine the class project.